Pengaruh Pengawasan Terhadap Kinerja Pegawai Pada Dinas Satuan Polisi Pamong Praja Kabupaten Pegunungan Arfak - Mei Hastuti; Seprin Pareda; Stelly Morasa; Eirene Mantiri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The type of research used in this research is survey research, with a quantitative approach, a questionnaire as a data collection tool containing structured statements given to respondents. The number of samples determined in this study was 52 people using the Slovin formula. The data analysis used is Correlation and Simple Linear Regression analysis. From the analysis carried out it is obtained that rxy=0.969 states that the correlation between variable X (Supervision) and Variable Y (Employee Performance) can be interpreted as a very strong correlation and the contribution of variable X to variable Y is 94 %. The results of the regression test obtained a value of a = 2.455 and a value of b = 0.943, so this was substituted into the linear regression formula: Ŷ = 2.455 + 0.943 ) Employee Performance is 2,455. The regression coefficient (B) = 0.943 states that for every additional value of the variable (X) Supervision, it is predicted that the value of the variable (Y) Employee Performance will increase by 0.943.